CLINICAL PROFILE AND OUTCOME OF INFANT OF DIABETIC MOTHER IN A TERTIARY CARE CENTRE - Shah, Madhu; Poudel, Saurav; Parajuli, Bivusha; Yadav, Muskan (Journal of Chitwan Medical College, 2024)
Background: Diabetes poses risks during gestation, with 80% attributed to gestational diabetes mellitus. It leads to complications from pre-conception to long-term. Infants born to diabetic mothers face various challenges, from spontaneous abortions to congenital anomalies. The study aimed to assess the clinical profile and outcome of the infants born to diabetic mothers at Nobel Medical College. Methods: This was a prospective observational study carried out in the Department of Pediatrics, Nobel Medical College Teaching Hospital, Biratnagar from September 2022 to August 2023. Consecutive sampling was done to include infants born at our institute to diabetic mothers. Variables like demographic and obstetric profile of the mothers, sex of the newborn, mode of delivery, birth weight, complications, and outcome were collected. Descriptive data analysis was done using SPSS Version 29. Results: A total of 79 infants born to diabetic mothers at our institute were studied. Of them, 18 (21.52%) were born to prediabetics and 61 (78.44%) to mothers with gestational diabetes. There were 42 (53.16%) male and 37 (46.84%) female. Twenty-six (32.91%) were born preterm, and LSCS was required in 41 (51.89%) cases. Sixteen (20.25%) were large for gestational age. Fifty-five (69.62%) developed one or multiple complications while 44 (55.7%) required NICU admission. The most common was hypoglycemia, followed by respiratory complications seen in 19 (24.05%) and 16 (20.25%) respectively. Conclusions: Diabetes during pregnancy is associated with various complications for the infant. A timely diagnosis and proper glycemic control of the mother are of great importance in the reduction of complications.